Bis[N-(3-aminopropyl)propane-1,3-diamine-κ3N,N′,N′′]cadmium nitrate perchlorate - Václav Eigner; Michal Dušek; Yunes Abbasityula; Hamid Goudarziafshar; Mohsen Nikoorazm (Acta Crystallographica Section E, 2012)
The title complex, [Cd(C6H17N3)2](ClO4)(NO3), was synthesized by the reaction of Cd(NO3)2·4H2O, bis(3-aminopropyl)amine and sodium perchlorate in methanol. The asymmetric unit of the title complex consists of one Cd2+ cation, two tridentate bis(3-aminopropyl)amine ligands, one nitrate anion and one perchlorate anion. The Cd2+ cation is coordinated by six N atoms of the bis(3-aminopropyl)amine ligands in a slightly distorted octahedral coordination geometry. In the crystal, molecules are held together by an intricate network of N—H...O interactions. One of the two amine ligands was found to be disordered over two sets of sites, with a ratio of 0.802 (3):0.198 (3), similarly to the nitrate anion, with a ratio of 0.762 (10):0.238 (10).